COMPARISON OF LIPID LOWERING EFFECTS OF ROSUVASTATIN AND ATORVASTATIN IN TYPE 2 DIABETIC PATIENTS WITH PRIMARY HYPERLIPIDEMIA - Shabbir, Safina; Humayun, Zill -e-; Yousaf, Muhammad Javad; Manzar, Muhammad Adnan; Mushtaq, Shabana; Yousaf, Maria (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate & compare the mean change in fasting serum total cholesterol and LDL-C levels from baseline, after 12 weeks of oral treatment with oral Rosuvastatin and with Atorvastatin in type 2 diabetic patients with primary hyperlipidemia. Study Design: Cross sectional comparative study. Place and Duration of Study: The present study was conducted in the Medicine Department, Pakistan Naval Ship, Shifa Hospital, Karachi, from Mar to Sep 2016. Methodology: The sample was collected by non- probability convenient sampling. The total of 114 DM type 2 patients were randomly divided into two equal groups. Group A was given Rosuvastatin whereas group B was given Atorvastatin orally daily for 12 weeks along with oral treatment for diabetes. After 12 weeks, Fasting Serum Total Cholesterol and Serum LDL-C were estimated, and noted as final levels. Results: There was greater reduction in terms of mean change in serum total cholesterol levels and low-density lipoprotein – cholesterol (LDL-C) levels with Rosuvastatin as compared to Atorvastatin in type 2 diabetic patients with hyperlipidemia. Conclusion: Rosuvastatin can significantly improve lipid profile as compared to Atorvastatin in type 2 diabetic patients with hyperlipidemia.